Screening nostalgia : populuxe props and technicolor aesthetics in contemporary American film - Sprengler, Christine (New York : Berghahn Books, 2009)
In this fascinating in-depth study of the impact of nostalgia on contemporary American cinema, Christine Sprengler unpicks the history of the concept and explores its significance in theory and practice. She offers a lucid analysis of the development of nostalgia in American society and culture, navigating a path through the key debates and aligning herself with recent attempts to recuperate its critical potential. This journey opens up the myriad permutations of nostalgia across visual and material culture and their interface with cinema, with the 1950s emerging as a privileged moment.
Introduction -- Setting the stage: the history of nostalgia -- The fifties: nostalgia's privileged object and the origins of its dominant American strain -- The nostalgia film in practice and theory -- Sin city: reading the tails of a populuxe prop -- Far from heaven: creative agency, social history and the expressive potential of costume -- The aviator: deliberate archaism, technicolor aesthetics and style as substance -- Conclusion: The good German and the good of nostalgia.
Includes bibliographical references (pages 180-189) and index.
Filmography: pages 175-180.
Print version record.
JSTOR
Keywords: Nostalgia in motion pictures; Motion pictures -- Aesthetics; Motion pictures -- United States -- History -- 20th century; Nostalgie au cinéma.; Cinéma -- Esthétique.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- Direction & Production; Motion pictures; Motion pictures -- Aesthetics; Nostalgia in motion pictures; United States; 1900-1999; History